Prudential Liquidity Regulation in Developing Countries : A Case Study of Rwanda - Sanya, Sarah (IMF Working Papers; Working Paper ;, 2012)
This paper analyses the prudential liquidity management framework, in particular the quantitative indicators employed by the central bank of Rwanda in response to the domestic liquidity crisis in 2008/09. It emphasises that the quantitative methods used in the monitoring and assessment of systemic liquidity risk are inadequate because they did not signal the liquidity crises ex-post. There are quick gains to be made from augumenting the liquidity risk indicators with more dynamic liquidity stress tests so that compliance will be achieved through lengthening the maturities of both assets and liabilities on the balance sheet as opposed to simply holding more liquid assets. The paper recommends that policy emphasis shift toward reforms that strengthen systemic liquidity risk assesment, monetary policy implementation as well as improve the efficiency of Rwanda's financial system.